Influence of Deep Invasive Tumor Thrombus on the Surgical Complexity and Prognosis of Patients With Non-Metastatic Renal Cell Carcinoma Combined With Venous Tumor Thrombus - Zhao, Xun; Yan, Ye; Dong, Jing-han; Liu, Zhuo; Zhang, Hong-xian; Liu, Cheng; Ma, Lu-lin (Frontiers in Oncology, 2022)
Background: To evaluate the impact of deep invasive tumor thrombus (DITT) on the surgical complexity and prognosis of patients with renal cell carcinoma with venous tumor thrombus. Methods: We retrospectively reviewed clinical data of 138 patients with non-metastatic renal cell carcinoma combined with venous tumor thrombus, who underwent surgical treatment in Peking University Third Hospital from January 2015 to June 2020. Patients were divided into the DITT group (84 patients) and non-invasive tumor thrombus (NITT) group (54 patients). Chi-square, t test and Mann-Whitney U test were used for categorical and continuous variables respectively. Kaplan-Meier plots were performed to evaluate the influence of DITT. Univariable and multivariable Cox regressions were conducted to determine independent prognostic factors and then assembled to make a nomogram to predict the survival. The performance of the nomogram was evaluated by Harrell's consistency index (C-index). Results: Deep invasive tumor thrombus significantly increase the difficulty of surgery for patients with renal cell carcinoma with venous tumor thrombus, which is mainly reflected in longer operation time (P<0.001), more surgical bleeding (P < 0.001), a higher proportion of perioperative blood transfusion (P = 0.006), a higher proportion of open surgery (P = 0.001), a longer postoperative hospital stay (P = 0.003), and a higher proportion of postoperative complications (P = 0.001). DITT (hazard ratio [HR] = 2.781, P = 0.040) was one of the independent risk factors for worse prognosis. Multivariate analysis showed that sarcoma-like differentiation (P = 0.040), tumor thrombus invasion (P = 0.040), low hemoglobin (P = 0.003), pathological type (P <0.001) were independent prognostic factors. The nomogram, combining all these predictors, showed powerful prognostic ability with C-index of 78.8% (CI: 71.2-86.4%). The predicted risk closely matches the observed recurrence probability. Conclusion: Deep invasive tumor thrombus significantly increased the difficulty of surgeries for patients of renal cell carcinoma with venous tumor thrombus, and may lead to poor prognosis.